2012
DOI: 10.1109/tmag.2012.2207707
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Magnetorheological Fluid Properties at Shear Rates of up to 25 000 s$^{-1}$

Abstract: Magnetorheological energy absorbers (MREAs) have been successfully deployed in occupant protection systems to protect against potentially injurious shock, crash and blast loads. These MREAs operate at shear rates upwards of 25 000 s , but magnetorheological fluids (MRFs) are typically characterized for shear rates up to 1000 s in commercially available parallel counter-rotating disk rheometers. Because of the lack of availability of data at the required high shear rates, a Searle-type magnetorheometer (essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…It showed that the internal pressure generated in an FF subjected to a magnetic field is not strong enough to be relevant for use as an active lubricant in most journal bearing applications. The work of Becnel et al (2012) showed that the magnetoviscous effect is still present at shear rates up to 25,000 s 21 , a value that is regularly observed in bearing system applications. However, Urreta et al (2010) showed that the gain of using an MR fluid at high shear rates diminishes due to the large viscous stresses at higher speeds.…”
Section: Introductionmentioning
confidence: 84%
“…It showed that the internal pressure generated in an FF subjected to a magnetic field is not strong enough to be relevant for use as an active lubricant in most journal bearing applications. The work of Becnel et al (2012) showed that the magnetoviscous effect is still present at shear rates up to 25,000 s 21 , a value that is regularly observed in bearing system applications. However, Urreta et al (2010) showed that the gain of using an MR fluid at high shear rates diminishes due to the large viscous stresses at higher speeds.…”
Section: Introductionmentioning
confidence: 84%
“…Originally validated using low shear rate γ̇< − ( 1000 s ) 1 measurements, it was later shown to hold true in high shear rate operation [6] in carefully controlled laboratory experiments. It is proposed here that this nondimensional analysis can be effectively extended to model practical MREA devices under real-world conditions.…”
Section: Mason Number and Apparent Viscositymentioning
confidence: 95%
“…Both MR yield stress and fluid viscosity have been shown to vary with temperature [4,5]. Furthermore, MRFs are highly shear thinning materials, so they exhibit a significant reduction in viscosity as shear rate increases [6]. For these reasons, a wide variety of fluid characterization tests, which vary temperature, shear rate, and applied magnetic field are currently required to adequately determine the performance of a given MR fluid utilized in certain devices and environments, and consequently, predictive models such as the Herschel-Bulkley (HB) constitutive model typically employed to characterize measured rheological behavior must rely on a huge data set of characterization tests to be useful across the entire range of expected operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above discussion, the flow characteristics of MRG-70 can be described by the Herschel–Bulkley model (equation (1)), which is slightly modified from the Bingham fluid model (equation (2)) 2729 where τ is the shear stress, τ y , is the shear yield stress, r· is the shear rate, η is the viscosity, k is the consistency coefficient, and n is the non-Newtonian exponent. Different values of n represent different characteristics, as follows …”
Section: Preparation Of Mrg and Its Steady-state Shear Testmentioning
confidence: 99%